2017
DOI: 10.1089/dna.2017.3643
|View full text |Cite
|
Sign up to set email alerts
|

Synergetic Neuroprotective Effect of Docosahexaenoic Acid and Aspirin in SH-Y5Y by Inhibiting miR-21 and Activating RXRα and PPARα

Abstract: Parkinson's disease (PD) is a serious neurodegenerative disorder that lacks effective therapeutic methods. In this research, expressions of PPARα, RXRα, and miR-21 were evaluated in PD patients and normal controls. To investigate the effects of miR-21, docosahexaenoic acid (DHA) and aspirin (ASA) on PD, as well as the relationships between them, SH-Y5Y cells were treated with DHA, ASA, or both for 24 h. The assay showed that levels of miR-21 were increased and levels of PPARα were decreased in PD patients comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 30 publications
2
30
0
1
Order By: Relevance
“…Importantly, the study showed that DHA increased neurotrophic factors such as GDNF and BDNF. Thus, authors hypothesized that DHA upregulates PPARα expression by miR-21 inhibitor and activates RXRα, which reveals induced BDNF, functioned as a neuroprotective factor [60].…”
Section: Bdnf Associated Micrornas In Parkinson's Diseasementioning
confidence: 99%
“…Importantly, the study showed that DHA increased neurotrophic factors such as GDNF and BDNF. Thus, authors hypothesized that DHA upregulates PPARα expression by miR-21 inhibitor and activates RXRα, which reveals induced BDNF, functioned as a neuroprotective factor [60].…”
Section: Bdnf Associated Micrornas In Parkinson's Diseasementioning
confidence: 99%
“…We assume that an increase of methylglutarylcarnitine reflects increased peroxisomal oxidation, such a metabolite having been suggested as a marker of this process [50]. ASA is known to induce peroxisome proliferator-activated receptor alpha expression and activity [51], thus boosting β-oxidation. Moreover, ASA-AMPK activation switches off ATP-consuming processes, while switching on catabolic pathways that generate ATP, a major event in the fatty acid oxidation process [52].…”
Section: Discussionmentioning
confidence: 99%
“… èññëåäîâàíèè [25] îöåíèâàëè ýêñïðåññèþ PPAR-a, ÿäåðíîãî ðåöåïòîðà RXRa, è ìèêðîÐÍÊ miR-21 ó ïàöèåíòîâ ñ ÁÏ ïî ñðàâíåíèþ ñ êîíòðîëüíîé ãðóïïîé. Óñòàíîâëåíî, ÷òî ñî÷åòàíèå äîêîçàãåêñàåíîâîé êèñëîòû (DHA) è ÀÑÊ ñìîãëî çíà÷èòåëüíî óëó÷øèòü ýêñïðåññèþ áåëêà PSD-95, íåéðîòðîôè÷åñêèõ ôàêòîðîâ BDNF è GDNF ïðè ïîâûøåíèè ãåòåðîäèìå-ðèçàöèè PPAR-a è RXRa, ÷òî ìîaeåò ÿâëÿòüñÿ íîâûì ïîäõîäîì ê ëå÷åíèþ ÁÏ.…”
Section: òå÷åíèå áåðåìåííîñòè è çàìåäëåíèå ðîäîâîé äåÿòåëüíîñòèunclassified